Estimation of inelastic skeletal storativity based on SAR-derived land subsidence and groundwater variation in Beijing Plain, China - Chenxia Li; Yanbing Wang; Jie Yu; Huili Gong; Xiaojuan Li; Xiyue Yang; Haowen Cheng; Xiaohuan Li; Kemiao Shao (Journal of Hydrology: Regional Studies)
Study region: Beijing plain in the eastern of Beijing, China. Study focus: Over the past three decades, more than 2 billion m3 of groundwater have been pumped annually in the Beijing Plain, resulting in approximately 431 km2 of land subsidence of more than 50 mm annually. While most studies have identified a correlation between land subsidence and groundwater overexploitation, quantifying their relationship has been challenging. In this paper, the land subsidence data were obtained based on the persistent scatterer interferometric synthetic aperture radar (PS-InSAR, PSI) and the least square (LS) method. The parameter of inelastic skeletal storativity (Si) of the confined aquifer was used as a quantitative indicator to describe the relationship between land subsidence and groundwater exploitation in the Beijing Plain. New hydrology insights: Moreover, the paper found a robust correlation between groundwater overexploitation and land subsidence in the deep confined aquifer through groundwater monitoring data. From 2005–2016, Si showed a gradual and continuous increase in a specific range. The abnormal change in Si value during 2014–2015 may be associated with the recharge of shallow confined and unconfined aquifers in the Beijing Plain by the South-to-North Water Diversion Project. The Si estimated in the study area can be utilized to accurately deduce the regional water level shifts, thereby aiding in the efficient and sustainable management of groundwater resources.